Connection between TQM and HRM in the Malaysian private SMEs - Sarwar, Abdullah; Chin Hooi, Partick Soh; Haque, A. K. M. Ahasanul (IDOSI Publications, 2016)
This study examined the extent to which Malaysian private SMEs differentiate in the way they utilize their HR. As a first step towards detecting the underlying standards of a quality-driven HR performance evaluation system, this study investigated the key issues currently existed in Malaysian SMEs in relation to HR performance evaluation systems. In this study, adapted questionnaires were utilized for data collection. The target respondents were the employees and the administrators involved in Malaysia private SMEs. The sample size for this study was 327 which were gathered through random sampling technique. This study delivers a deeper understanding on the influence of HRM components in implementing TQM practices in Malaysian Private SMEs. Therefore, both government and private SMEs can consider this as a useful companion to design appropriate policies that aim to improve organizational performance.